The barriers and ideas of improvement to community oriented policing (COP) development and implementation in Malaysia. Case study: Pulau Pinang, Malaysia - Hassan, Mohammad Mujaheed; Abdullah, Aldrin (The International Journal of Social Sciences and Humanities Invention, 2018)
Malaysia has adopted a method of policing, which is similar to the British’s Neighborhood Policing Teams (NPTs) called as Community-Oriented Policing (COP) in Malaysia. Community-oriented policing has been introduced to create a safer living environment. This concept is based on a partnership between police department and the communities, in which both parties will share the responsibility to identify, reduce, eliminate and prevent problems concerning community safety and order. Therefore, the spirit of community empowerment, smart ship, and interdependency between all stakeholders, including community, police, NGOs, and other interested parties are very much needed in this country through active and passive ways.